Taro-Leaf Inspired Patterning of Oleophobic Surfaces with High Wear Resistance - Hiroshi Tani (Japanese Society of Tribologists, 2018)
The lotus and taro leaf surfaces are superhydrophobic. We fabricated different surface patterns of lotus and taro leaves on Si surfaces and compared their contact angles and tribological properties. Three types of lotus patterns, consisting of a simple dot matrix of circular pillars with different pitches, and six types of taro patterns having the pillars distributed within a field of hexagonal ridges with different central pillar diameters and pitches, were prepared. The contact angles of water and hexadecane on these patterns were measured, and the wear resistance of each pattern was evaluated by reciprocating wear tests. The taro pattern showed a significantly higher contact angle for hexadecane and a lower coefficient of friction than the lotus pattern. The taro pattern ridges are supposed to contain air in the valleys between the ridges and pillars, which prevented sticking between the pillars and cloth fibers. Thus, the taro pattern exhibits better oleophobicity and a lower frictional force.